A Study to Evaluate the Effectiveness of a Structured Teaching Program on Knowledge of Nursing Care of Pacemaker Implantation Patients among IV Year B. Sc., Nursing Students in Selected Colleges in Mysore - S, Deepthi (Indian Journal of Nursing Sciences, 2024)
Aim: The study aimed to evaluate the effectiveness of a structured teaching program on knowledge of nursing care of pacemaker implantation patients among IV year B.Sc., nursing students in selected colleges in Mysore. Material and Methods: Evaluator research approach was selected for this study. The experimental one group pre-test, post-test design used. The study was conducted in two nursing colleges at Mysore, population in the study was IV year B.Sc., nursing students. The sample of the study was 60 IV year B. Sc., nursing Students. A simple random sampling technique was used to select the samples for the study. Result: The study’s findings indicate that the implementation of the structured teaching program, the average overall knowledge of IV year Basic B.Sc., and nursing students regarding nursing care of pacemaker implantation patients was 42.96%, with a mean of 10.74 and a standard deviation of 3.24. Consequently, it was observed that 70% of the students possessed inadequate knowledge, while 30% had moderately adequate knowledge. None of the students demonstrated adequate knowledge in this area. Following the implementation of the structured teaching program, the students’ knowledge on nursing care of pacemaker implantation patients increased by 42.96%. The analysis yields a net benefit of 42.96% in terms of knowledge acquisition. Conclusion: The study’s findings indicate a notable disparity in pre-test and post-test knowledge scores regarding the care of patients among 4th-year B.Sc., nursing students. It can be stated that the implementation of structured teaching program on the subject of nursing care for patients with pacemaker implants was successful in enhancing knowledge.